MAKNA SYARAT DAN UNSUR SILEK DESA KUBU GADANG - Rosaliza, Mita; Wardhana, Muhammmad Fajar Vierta; Risdayati, Risdayati (Jurnal Ilmu Budaya, 2020)
The martial art of silat in Minangkabau, which is usually called silek, has its own uniqueness in terms of terms and movements. Silek in Minangkabau is a legacy from the Minangkabau ancestors that still exists and develops today. The requirements that must be possessed in this silat include cloth, knives, sewing needles, mirrors, rice and money that have meaning in this silat tradition. In addition, there are other elements in these martial arts which also have meaning in terms of movement, clothing and place of implementation. This study focuses on the meaning of the terms and movements used in the silek of Tuo gunuong in Kubu Gadang village. The informants in this study are traditional elders and people who still practice silat as a martial art and understand the terms and meanings of the movement.